System and method of image processing for ultra-low bandwidth audio - Soryal, Joseph (2025)
Aspects of the subject disclosure may include, for example, a device, including a processing system including a processor; and a memory that stores executable instructions that, when executed by the processing system, facilitate performance of operations of receiving an original audio signal for an interval; creating a time-series graphical image of the original audio signal for the interval; compressing the time-series graphical image, thereby creating a reduced resolution image; recreating a retrieved audio signal from the reduced resolution image; determining whether a comparison of the retrieved audio signal to the original audio signal meets a quality threshold; responsive to meeting the quality threshold, compressing the reduced resolution image further and repeating the recreating and determining steps; and transmitting a last reduced resolution image that meets the quality threshold. Other embodiments are disclosed.